Device circuit co-design issues in FETs - Tayal, Shubham (CRC Press, 2024)
This book provides an overview of emerging semiconductor devices and their applications in electronic circuits, which form the foundation of electronic devices. Device Circuit Co-Design Issues in FETs provides readers with a better understanding of the ever-growing field of low-power electronic devices and their applications in the wireless, biosensing, and circuit domains. The book brings researchers and engineers from various disciplines of the VLSI domain together to tackle the emerging challenges in the field of engineering and applications of advanced low-power devices in an effort to improve the performance of these technologies. The chapters examine the challenges and scope of FinFET device circuits, 3D FETs, and advanced FET for circuit applications. The book also discusses low-power memory design, neuromorphic computing, and issues related to thermal reliability. The authors provide a good understanding of device physics and circuits, and discuss transistors based on the new channel/dielectric materials and device architectures to achieve low-power dissipation and ultra-high switching speeds to fulfill the requirements of the semiconductor industry. This book is intended for students, researchers, and professionals in the field of semiconductor devices and nanodevices, as well as those working on device-circuit co-design issues.
Keywords: bicssc / Electronic devices & materials; bicssc / Mathematical modelling; bicssc / Electrical engineering; bicssc / Microwave technology; bisacsh / TECHNOLOGY & ENGINEERING / Electrical